The intermediary effect of work stress on the relationship between off-duty professional growth and reflective ability among mid- and senior-level nurses - Junxian Wu; Jingru Song; Mingfang Zhang; Lin Li; Qin Shen (BMC Nursing)
Abstract Background Mid- to senior-level nurses play a pivotal role in healthcare. Their reflective ability is crucial for clinical decision-making and the continuous improvement of nursing practices. Although numerous studies have emphasized the importance of enhancing reflective ability among mid- to senior-level nurses, the specific relationship between off-duty professional growth, dual work stress, and reflective ability remains unclear. Objective This study aims to investigate the relationship between reflective ability, work stress, and off-duty professional growth among mid- to senior-level nurses in China, and to determine the mediating role of work stress. Methods A convenience sampling method was used to recruit 534 mid- to senior-level nurses from three tertiary hospitals in Jiaxing, Zhejiang Province. Data were collected and analyzed using a general information questionnaire, the Leisure Crafting Scale, the Challenge-Hindrance Work Stress Scale, and the Clinical Nurse Reflective Ability Scale. Results The mean scores for leisure crafting, challenge stress, hindrance stress, and reflective ability among mid- to senior-level nurses were 23.82 ± 9.17, 16.97 ± 6.49, 16.65 ± 5.44, and 56.26 ± 19.09, respectively. Leisure crafting was positively correlated with reflective ability (r = 0.389, P < 0.001), challenge stress (r = 0.399, P < 0.001), and negatively correlated with hindrance stress (r = -0.367, P < 0.001). Reflective ability was positively correlated with challenge stress (r = 0.350, P < 0.001) and negatively correlated with hindrance stress (r = -0.417, P < 0.001). Both challenge-and hindrance stress partially mediated the relationship between leisure crafting and reflective ability, with mediation effects of 19.7% and 30.8%, respectively. Conclusion This study demonstrates that the reflective ability of mid- to senior-level nurses in China is currently at a moderately low level. Enhancing Off-duty professional growth, leveraging the beneficial aspects of challenge stress, and reducing the negative effects of hindrance stress can notably improve reflective ability. These efforts can lay a strong foundation for the continuous enhancement of nursing quality.